Direct and indirect written corrective feedback on the use of past tense amongst ESL learners / Tang Tuck Mun - Tang , Tuck Mun (2020)
For decades, a considerable amount of attention has been given to written corrective feedback (WCF) in the field of second language acquisition (SLA). In the early development of WCF, Truscott (1996) raised a few theoretical issues which led studies on WCF to be carried by researchers opposing his claims. He claimed that 1) a simple transfer of information cannot be expected to be beneficial due to the well-established SLA insights about the complex and gradual nature of the process of acquisition, 2) if WCF approach is employed at a time that is not consistent with the natural order, it could not be effective and 3) an ESL learner learns anything from the employment of WCF approach, the learning is likely to be only ‘pseudo-learning.’ Hence, this study aimed to explore the extent to which ESL learners’ accuracy in past tense use improves as a result of direct and indirect WCF and other factors that may contribute to ESL learners’ accuracy in past tense use resulting from direct and indirect WCF. A mixed-method design was employed in this study. Quantitative data was collected using a pre-test, an immediate post-test, and a delayed post-test whilst qualitative data was collected via interviews. A total of eighty UM undergraduates took part in this study, and they were divided into two treatment groups equally. Both groups were given direct and indirect WCF, respectively. The analysed quantitative data showed that the direct WCF group performed better than the indirect WCF group. As for the qualitative data, three main themes (factors) emerged from the thematic analysis. They were learners’ attitudes toward the WCF provided, learners’ thinking effort, and scaffolding. Findings from this study cannot be generalised as the study collected data only from one local university in Malaysia.